Development of the Nature-Reserved Fund of Ukraine on the Basis of the Best Polish Experience - Yakymchuk, Alina; Valyukh, Andriy; Pustovit, Nataliia; Yakymchuk, Oleh (<center>Conference Proceedings Determinants Of Regional Development</center>; No 3 (2022): Conference Proceedings - IX International Scientific Conference Determinants of Regional DevelopmentDO - 10.14595/CP/03/007, 2022)
Nature loss presents risks to future human prosperity and well-being of all nations. That is why every nation, sector and person play a key role in protecting the nature. Taking into account the fact that nature protection is a global problem, adaptation of national standards with European directives will make it possible to unify the financial support for the development of natural-protection fund (NPF) in Ukraine. Today the priority direction of Ukraine’s foreign policy is the ratification of the agreement with the EU, the harmonization of national legislation on the nature protection preservation with European directives. COVID-19 and other high-threat destabilizing factors combine to constitute to the negative impact on economic condition of the EU states. The main objectives of this work are to integrate different knowledge and research from diverse sectoral, geographical, historical, political, managerial and institutional perspectives and to develop an efficient system of preserving ecosystems, in particular to implement of international experience and to improve the socio-cultural development level of Ukraine in the context of sustainable development. The object of study is nature-protected fund as the country’s national wealth, while the subject of study is the process of development of Ukraine’s nature-protected fund on the example of Poland’s financing and positive experience under the conditions of climate change. The factor analysis of indicators on financing of NPF in Ukraine and Poland has been carried out. The main factors of NPF financing efficiency in the Republic of Poland and Ukraine have been compared. The main problems of state financing of nature-protected fund in Ukraine have been revealed. The measures to improve state financing of nature-protected fund in Ukraine on the best Polish experience base have been proposed. The correlation-regression modeling of environmental expenditures conducted in the work allowed to identify certain reserves for improving the economic and financial indicators of nature conservation in Ukraine in the long run to offset the negative impact of the COVID-19 pandemic. Furtheremore, on the basis of correlation-regression analysis between current environmental costs and innovation costs, conclusions were made on the effectiveness of environmental costs in Ukraine.